HAKIKAT, TUJUAN DAN FUNGSI PENDIDIKAN ISLAM DI ERA MODERN - Nita Zakiyah (AS-SALAM, 2012)
In fact, islamic education came by efforting to answer moslem’s issues,especially for this era and for the next without skipping the reference toguiding Al-Qur’an nad Sunnah. This case is being the main topic of thisstudy. On islam, an education is a derivation from the texts of Al-qur’anand rasul’s Sunnah. So Islamic Education does not only for the secularorientation, but also implements the useful education (ilm nafi’) in realizinghuman character as khalifatulah. This conception is esence, tendention, andfunction of islamic education in modern era which are based on greatnessof iliahiyah in humanistic dimension and sains in this modern era.